Too many migrants, too few services : a model of decision-making on immigration and integration with cultural distance - Harrie A. A. Verbon; Lex Meijdam (Center for Economic Studies and ifo Institute (CESifo), 2004)
In this paper we model the demand for immigrants as a trade-off native voters face between having services, produced by unskilled and non-assimilated immigrants, and experiencing disutility due to the immigrant workers having a culture different from the native culture. Immigrants decide whether to integrate into the native culture. If they don?t, they produce services. Assimilated immigrants take on skilled jobs. At the political level natives choose the number of immigrants that can be allowed, given some fixed price for services. We show that, at the assumed price, it is never optimal for natives to have equilibrium or unemployment in the service sector. Market forces then lead to higher service prices, implying that the initially allowed number of immigrants is too large.
Keywords: D72; F22; 330; Migrationspolitik; Einwanderungsrecht; Soziale Integration; Dienstleistung; Ungelernte Arbeitskräfte; Kulturpsychologie; Wohlfahrtseffekt; Theorie